IEEE INFOCOM Workshops 2009 2009
DOI: 10.1109/infcomw.2009.5072151
|View full text |Cite
|
Sign up to set email alerts
|

Graph-Based P2P Traffic Classification at the Internet Backbone

Abstract: Abstract-Monitoring network traffic and classifying applications are essential functions for network administrators. In this paper, we consider the use of Traffic Dispersion Graphs (TDGs) to classify network traffic. Given a set of flows, a TDG is a graph with an edge between any two IP addresses that communicate; thus TDGs capture network-wide interactions. Using TDGs, we develop an application classification framework dubbed Graption (Graph-based classification). Our framework provides a systematic way to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…For instance, But et al [2007] proposed the ANGEL system for detecting and then prioritizing game traffic in ISP network. Iliofotou et al [2009b] developed a graph-based framework for classifying P2P traffic. Armitage [2006a, 2006b] proposed training the classifier on a combination of short subflows for fast traffic classification and demonstrated that good classification results could be achieved with subflows formed by as few as only 25 packets.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, But et al [2007] proposed the ANGEL system for detecting and then prioritizing game traffic in ISP network. Iliofotou et al [2009b] developed a graph-based framework for classifying P2P traffic. Armitage [2006a, 2006b] proposed training the classifier on a combination of short subflows for fast traffic classification and demonstrated that good classification results could be achieved with subflows formed by as few as only 25 packets.…”
Section: Related Workmentioning
confidence: 99%
“…First, since our techniques are applied at the structure-level via graph analysis, they will also identify regular P2P file-sharing topologies. To avoid misclassifying such regular P2P networks as botnets, we can perform preprocessing such as flow filtering and clustering [9] based on known patterns of regular P2P networks such as the port numbers. Also, bots identified locally in edge networks are helpful as their presence in a communication graph makes other nodes suspicious as well, so our approach may need assistance from detection mechanisms at the edge to further confirm that a graph is indeed formed by a botnet.…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, all edges carry the same weight. Graph metrics to determine whether the traffic is P2P are proposed in [9] and adopted to analyze the modified chord in [11]. In our analysis, we inspect the same set of features as in [11] for consistency.…”
Section: F Graph Analysismentioning
confidence: 99%
“…We gathered information from two groups: the authors of the papers that [ Annapureddy et al 2007b;Yunhao et al 2007;Xie et al 2008;Mol et al 2008;Silva et al 2008;Iliofotou et al 2009;Pianese et al 2007;Annapureddy et al 2007a;Leonardi et al 2008;Doulkeridis et al 2007a;Cheng et al 2007;Chi et al 2007;Rowaihy et al 2007;Ahmed and Boutaba 2007;Belenkiy et al 2007;Kantere et al 2009;Huang et al 2007b;Garbacki et al 2007;Buchegger et al 2009;Crainiceanu et al 2007;Zhou and Hwang 2007;Bharambe et al 2008;Terpstra et al 2007;Zaharia and Keshav 2008;Wang et al 2007;Guo et al 2007;Hefeeda and Saleh 2008;Ren et al 2008;Zhou et al 2008;Zhuge and Li 2007;Haridasan and van Renesse 2008;Feng and Li 2008;Magharei and Rejaie 2009a;Liu 2007;Yang and Chen 2008;Do et al 2008;Do et al 2009;Boufkhad et al 2008;Duminuco and Biersack 2008;Yiu et al 2007;Doulkeridis et al 2007b;…”
Section: Features Questionnairementioning
confidence: 99%